Drug-related problems and pharmacist interventions in a cohort of patients with asthma and chronic obstructive pulmonary disease - İZZETTİN, FIKRET VEHBI; Apikoglu-Rabus, Sule; Yesilyaprak, Gozde; Izzettin, FİKRET VEHBİ (My University, 2016)
Background: Asthma and chronic obstructive pulmonary disease are preventable and treatable chronic airway diseases with high incidence and prevalence. Pharmacists and clinical pharmacy based pharmaceutical care services have positive impact on therapy outcomes.